ETIKA MENGKONSUMSI MAKANAN YANG TERTUANG DALAM HADITS SUNAN AT-TIRMIDZI NO. INDEKS 2302 - Syaiful Bahri; Budiyanto Budiyanto (LPPM Sekolah Tinggi Ilmu Al-Qur'an Wali Songo Situbondo, 2022)
Healthy is everyone's dream, because with healthy humans can carry out their activities smoothly. In Islam there is also a recommendation to live a healthy life, because if Muslims are healthy, the quality of their worship will automatically increase. So how does Islam guide its people to stay healthy? One of them is not to overdo it in eating, this is the focus of research in writing this thesis. This study uses a literature review which then after finding the results compares the hadith with health sciences. We can use the studied hadith as our guide or not to live a healthy life. Therefore, the problem that will be raised or researched is the takhrij hadith and the criticism of the sanad matan about food ethics contained in the hadith narrated by At-Tirmidhi, which is a reference that was appointed as research material. It is hoped that Muslims can actualize this hadith in real life as a manifestation that Muslims love their Prophet and as human instincts desire a healthy life which ultimately increases the quality of our worship. This research was carried out by mentakhrij hadith as research, after finding the results then comparing the hadith with health sciences. We can use the studied hadith as our guide or not to live a healthy life. In the end, this research will assess the quality of the hadith that is being researched so that it is feasible or not to be used as evidence and guidance for Muslims. In a hadith narrated by Imam At-Tirmidhi, it is sufficient for the son of Adam to fill his stomach with a third for food, a third for drink and a third for breathing. It is hoped that Muslims can actualize this hadith in real life as a manifestation that Muslims love their Prophet and as human instincts desire a healthy life which ultimately increases the quality of our worship.